Understanding the Role of Motivation in Professional Athletes - Michelle Gacio Harrolle; Melissa Klay (Journal of Applied Sports Management, 2019)
Our study examines the overall motivation of professional athletes in an effort to assist sport organizations in understanding their most important asset, the players. The purpose of this qualitative study was to investigate the experiences and motivations of professional athletes within a team setting. Researchers conducted individual semi-structured interviews with 13 professional American football players. Seven themes were present within the data including a love of the game, selfmotivation, sense of community, professional development, engagement with fans, assist the league, and lack of financial support, which was identified as a deterrent to motivation. Teams should increase investment in the professional development of players as valuable human resources to increase overall organizational success. Subscribe to JASM
Keywords: American football; human capital; motivation; professional athletes